Construction of a strong, fast self-healing adhesive for propellants based on the synergy of weak hydrogen bond array reorganization and disulfide exchange reactions. (16th January 2023) - Jing, Tu; Heng, Xu; Jingqing, Tian; Haozhe, Li; Li, Liang; Pingyun, Li; Xiaode, Guo
Abstract: Internal damage of propellant, especially interfacial debonding, can easily cause major accident and consume a lot of costs. Although some literatures describe the application of self-healing adhesives in the field of propellant, the mechanical properties are usually poor, and the application of self-healing adhesives on debonded interfaces has never been studied. In this work, a high-strength polyurethane adhesive with tensile strength greater than 10 MPa and rapid self-healing ability (recovery at room temperature for 24 h) was constructed based on multiple weak hydrogen bond arrays and highly active disulfide bonds. Importantly, we ground breakingly tested the self-healing effect for interfacial debonding. Benefiting from the high-strength adhesion of a large number of hydrogen bond arrays, the peel strength of the adhesive at the propellant interface is 140% higher than that of traditional adhesives. At the same time, it can effectively heal the debonded interface, and the peel strength is still higher than that of traditional adhesives even undergo secondary healing. Our work has implications for solving the industry's thorny - propellant interface debonding. Graphical abstract: The independent dual-active phase-separated structure results in high-strength mechanical properties and rapid self-healing capabilities. Image 1 Highlights: Unprecedented application of high-efficiency self-healing adhesives to healing propellant debonding interfaces. Independent reversible phase-separated structure stimulates high-strength mechanical properties and room temperature self-healing ability. Multiple hydrogen bonds contribute to strong bonding strength.